Cardiotocography pattern: not always a true friend - Aquino, Carmen Imma; Amadori, Roberta; Vaianella, Elisabetta; Bonassisa, Silvia; Libretti, Alessandro; Surico, Daniela; Remorgida, Valentino (Acta Biomedica Atenei Parmensis, 2023)
Fetal well-being in labor could be assessed trough cardiotocography (CTG). Some doubts have been raised about its unequivocal applicability. Pathological CTG is in most cases connected to fetal acidosis at birth, but other potential causes must be considered in the differential diagnosis.A 31-years-old G2P1 patient referred to our Department of Obstetrics and Gynecology for her scheduled post-term CTG at 40 weeks and 3 days of gestation. The pregnancy was uneventful. CTG was classified as suspicious, and after pharmacological induction, it switched as pathological: an emergency cesarean section was performed. Venous and arterial blood sample taken from the umbilical cord were normal. The next assessments revealed that Atrial Flutter (AFL) occurred at birth.Suspicious CTG is not always associated to neonatal asphyxia. Cardiotocography can help not only in the evaluation of fetal distress, but also in the assessment of global fetal cardiac activity.The presence of a fetal heart defect should be considered when CTG is suspicious.